Compassion in a heartbeat: Physiology during couples' loss discussions. (June 2019) - Corner, Geoffrey W.; Saxbe, Darby E.; Chaspari, Theodora; Rasmussen, Hannah F.; Perrone, Laura; Pettit, Corey; Friendly, Madeleine; Timmons, Adela C.; Margolin, Gayla
The physiology of compassion, typically studied in individuals, has not yet been studied dyadically and in the context of close relationships. The current study used dating partners' discussions of personal losses to simultaneously investigate the physiological profile of compassion in an individual sharing an emotionally salient loss, the "narrator, " and his or her partner, the "listener." In a given moment, listeners who perceived themselves as being more compassionate had a lower heart rate. This association was stronger for listeners whose partners were less anxiously attached. Narrators and listeners who were more avoidantly attached showed stronger positive associations between their average heart rate and overall compassion. Additionally, narrators' compassion moderated linkage between partners' heart rates such that heart rates were more strongly linked in moments with lower levels of compassion. These results support studying compassion dyadically and illustrate the importance of attachment style in the physiology of compassion.